Answer: see proof below
Explanation:
Given: A + B + C = π → A + B = π - C
A + C = π - B
B + C = π - A
Use the Cofunction Identity: sin A = cos (π/2 - A)
Use the following Sum to Product Identity:
sin A + sin B = 2 sin [(A + B)/2] · cos [(A + B)/2]
Use the Double Angle Identity: sin 2A = 2 sin A · cos A
Proof LHS → RHS
LHS: sin (B + C - A) + sin (C + A - B) + sin (A + B - C)
Given: sin[(π - A) - A) + sin [(π - B) - B] + sin [(π - C) - C]
= sin (π - 2A) + sin (π - 2B) + sin (π - 2C)
= sin 2A + sin 2B + sin 2C
= (sin 2A + sin 2B) + sin 2C
![\text{Sum to Product:}\qquad 2\sin \bigg((2A+2B)/(2)\bigg)\cdot \cos \bigg((2A-2B)/(2)\bigg)+\sin 2C\\\\.\qquad \qquad \qquad \qquad =2\sin (A+B)\cdot \cos (A-B)+\sin 2C](https://img.qammunity.org/2021/formulas/mathematics/high-school/i6nx4t87acl74kmvnxr4odssi0tirnhotr.png)
![\text{Double Angle:}\qquad 2\sin (A+B)\cdot \cos (A-B)+2\sin C \cdot \cos C](https://img.qammunity.org/2021/formulas/mathematics/high-school/h6gcjaptisw00hltp5vet2y8hvbc4xwqjr.png)
Given: 2 sin C · cos (A - B) + 2 sin C · cos C
Factor: 2 sin C [cos (A - B) + cos C]
![\text{Sum Product:}\qquad 2\sin C\cdot 2\cos \bigg((A-B+C)/(2)\bigg)\cdot \cos \bigg((A-B-C)/(2)\bigg)\\\\.\qquad \qquad \qquad =2\sin C\cdot 2\cos \bigg(((A+C)-B)/(2)\bigg)\cdot \cos \bigg((A-(B+C))/(2)\bigg)](https://img.qammunity.org/2021/formulas/mathematics/high-school/lk39qmzxn34o4ususxqg5efyjs1zawwq6q.png)
![\text{Given:}\qquad \qquad 4\sin C\cdot \cos \bigg(((\pi -B)-B)/(2)\bigg)\cdot \cos \bigg((A-(\pi -A))/(2)\bigg)\\\\.\qquad \qquad \qquad =4\sin C\cdot \cos \bigg((\pi -2B)/(2)\bigg)\cdot \cos \bigg((2A-\pi)/(2)\bigg)\\\\.\qquad \qquad \qquad =4\sin C\cdot \cos \bigg((\pi)/(2)-B\bigg)\cdot \cos \bigg((\pi)/(2)-A\bigg)](https://img.qammunity.org/2021/formulas/mathematics/high-school/pz3s40vv54h5fo807beyrqwppnp5sdks8m.png)
Cofunction: 4 sin A · sin B · sin C
LHS = RHS: 4 sin A · sin B · sin C = 4 sin A · sin B · sin C
![\checkmark](https://img.qammunity.org/2021/formulas/mathematics/middle-school/2v4z11vsn0bdvhj920fbk7f97ux40axw6u.png)